Percutaneous screw fixation for painful non-union of lateral malleolus ankle fractures. Issue 10 (October 2018) - Batten, Timothy J.; Scott-Davies, Charlotte; Butler, Michael; Parsons, Stephen W.; Walter, Richard P.
Abstract: Introduction: Lateral malleolus non-union can cause pain and loss of function. Standard treatment involves open approach with debridement, bone-grafting and plate stabilisation, with published surgical site infection rates to 17%. To minimise the risk of soft tissue complications and allow early mobilisation, we describe a technique for percutaneous cannulated screw stabilisation. Materials and methods: Retrospective case review for all percutaneous lateral malleolus non-union stabilisation procedures undertaken in our hospital between 2011 and 2017 was performed. Fracture union was diagnosed by resolution of pain and swelling, with a return to full weight-bearing mobilisation and two-view radiographs consistent with union. Results: Twelve cases were reviewed. All fractures united. There was one superficial wound infection treated with oral antibiotics, and one early case with drill-piece fracture requiring conversion to open procedure with plate stabilisation. Conclusion: We believe this to be the first report of percutaneous stabilisation for non-union of lateral malleolus fractures. We demonstrate this to be a safe and effective technique.